2015
DOI: 10.1017/s0001924000011179
|View full text |Cite
|
Sign up to set email alerts
|

Total pressure distortion levels at the aerodynamic interface plane of a military aircraft

Abstract: Military aircrafts are often subjected to severe flight maneuvers with high Angles-of -Attack (AOA) and Angles of Sideslip (AOSS). These flight attitudes induce non-uniform in flow conditions to their gas turbine engines which may include distortion of inlet total pressure and total temperature at the Aerodynamic Interface Plane (AIP). Operation of the downstream compression system with distorted inflow typically results in reduced aerodynamic performance, reduced stall margin, and increased blade stress level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The process described herein is a part of a wider study (11), (21) the main objective of which is to estimate how the installed gas turbine engine's performance is affected by the aircraft's flight attitude. The airflow reaching the engine's face was predicted for each one of the examined flight attitudes and a total pressure profile at this plane was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The process described herein is a part of a wider study (11), (21) the main objective of which is to estimate how the installed gas turbine engine's performance is affected by the aircraft's flight attitude. The airflow reaching the engine's face was predicted for each one of the examined flight attitudes and a total pressure profile at this plane was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the current study, each one of the 27 CFD tested flight attitudes induced a total pressure distortion into the engine's face (AIP). This pressure distortion was quantified through the calculation of distortion descriptors in the way that has been described in detail in Triantafyllou et al 21 These distortion parameters can be correlated to the loss in surge pressure ratio (ÁPRS) in the way suggested by SAE AIR 1419. 12 ÁPRS is the loss in surge pressure ratio due to inlet distortion, normalised by the undistorted surge pressure ratio.…”
Section: Fan Stability Assessmentmentioning
confidence: 99%
“…where C t is the radial offset term for the tip. Based on the distortion descriptor results obtained in Triantafyllou et al, 21 the loss in surge pressure ratio (ÁPRS) for the examined flight attitudes is presented in Table 6. It is clarified that the flight attitudes with negative values of ÁPRS result in an increase in surge pressure ratio (relative to the uninstalled FAN) because in accordance with equation 3, in these cases the absolute value of the radial distortion component was greater than that of the circumferential distortion and since the radial distortion was negative in these cases the outcome of equation 3was also negative.…”
Section: Fan Stability Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, in this case, the air intake is integrated into the body. In another study, the effect of AoA and SSA has been numerically investigated for a military aircraft equipped with an S-type inlet [7]. The authors have shown that the flight attitudes induce non-uniformities on both the temperature and the total pressure distribution at AIP.…”
Section: Introductionmentioning
confidence: 99%